Implementasi Pendidikan Multikultural Guna Membangun Karakter Toleran Peserta Didik di MI Darussalam Poncol Magetan - Setiawan, Ferry; Kasanah, Mauridhatul (Edukhasi: Jurnal Inovasi Pendidikan, 2024)
Indonesia is a country that has various ethnicities, races, and religions gives rise to many different understandings and there are quite a few cases or problems regarding intolerance between those who have different understandings. So, with multicultural education, it is hoped that the school will contribute to overcoming the issues of racism, radicalism, and extremism. So this article will discuss how to apply multicultural education to build the tolerant character of students at MI NU Darussalam. This research uses qualitative research with interview, observation, and documentation data collection techniques. The results of this research are that the implementation of multicultural education at MI NU Darussalam has gone well. Tolerance has been taught to students from the start as part of character formation. Instilling multicultural values is carried out in various ways, both during learning and outside of learning. The success of this implementation is supported by the teacher's professionalism in integrating multicultural values into the learning process.